2022
DOI: 10.1371/journal.pone.0263585
|View full text |Cite
|
Sign up to set email alerts
|

The clinicopathology and survival characteristics of patients with POLE proofreading mutations in endometrial carcinoma: A systematic review and meta-analysis

Abstract: Background Endometrial carcinoma (EC) is classified into four distinct molecular subgroups. Patients with polymerase epsilon exonuclease domain mutated (POLE-EDM) tumors have the best prognosis of all. This meta-analysis consolidated the clinicopathology variations reported in the POLE-mutant subtype and survival parameters in patients with EC. Methods The following internet data bases were searched: PubMed, Web of science, Embase and Scimage directory. Data was extracted from eligible studies including samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…20,25 Individual patient data meta-analysis of all published and available international reports on POLEmut ECs showed that patients with confirmed pathogenic POLE mutations have almost no recurrence or disease-specific death events, even when their tumors appear to have unfavorable clinicopathologic or molecular characteristics, and adjuvant treatment was not associated with outcomes. 14 Excellent survival outcomes in POLEmut ECs were also confirmed in a more recent meta-analysis, 26 and in a 2022 publication from a Danish database in which patients with high-grade POLEmut ECs who received no adjuvant treatment encountered no recurrence events. 15 Taken together, these data support de-escalation of therapy in this molecular subtype.…”
Section: Development Of Pragmatic Classifiersmentioning
confidence: 76%
“…20,25 Individual patient data meta-analysis of all published and available international reports on POLEmut ECs showed that patients with confirmed pathogenic POLE mutations have almost no recurrence or disease-specific death events, even when their tumors appear to have unfavorable clinicopathologic or molecular characteristics, and adjuvant treatment was not associated with outcomes. 14 Excellent survival outcomes in POLEmut ECs were also confirmed in a more recent meta-analysis, 26 and in a 2022 publication from a Danish database in which patients with high-grade POLEmut ECs who received no adjuvant treatment encountered no recurrence events. 15 Taken together, these data support de-escalation of therapy in this molecular subtype.…”
Section: Development Of Pragmatic Classifiersmentioning
confidence: 76%
“…Therefore, efforts are required to minimize unnecessary adjuvant chemotherapy. The presence of POLE mutations in high-risk patients is an excellent example of this [ 58 ]. These patients may not need adjuvant chemotherapy even if SLN mapping identifies macroscopic lymph node metastasis; they may not require SLN mapping at all.…”
Section: Resultsmentioning
confidence: 99%
“…Longitudinal studies on patient-reported outcomes of adjuvant chemotherapy revealed that in patients with endometrial cancer, adjuvant chemotherapy is independently associated with increased fatigue, lymphedema, and neuropathy even after two years of treatment [58]. Therefore, efforts are required to minimize unnecessary adjuvant chemotherapy.…”
Section: Avenues For Future Researchmentioning
confidence: 99%
“…The patient underwent molecular analysis with immunohistochemistry, depicting positive POLE gene mutation and negative wild-type P53 and MSI. The presence of POLE demonstrates favorable prognostic possibilities, despite rare and high-grade tumours [7,8].…”
Section: Discussionmentioning
confidence: 99%